The grounds of affirmative action - Atrey, S (Johns Hopkins University Press, 2024)
On what grounds is affirmative action permissible? The apex courts of two of the world’s largest democracies have recently answered this question in seemingly diametrically opposite ways. In the case of India, the Supreme Court expanded the list of grounds of affirmative action to include economic status. In the case of the United States of America, the Supreme Court retracted its support for affirmative action based on race. Despite what may seem like contradictory positions, both courts undid affirmative action as a remedy for discrimination. The article explores how the courts’ fundamental misunderstanding of the meaning of grounds contributed to this. In particular, it interrogates the understanding of grounds such as caste and race exclusively in terms of social status and as divorced from material deprivation. Instead, the article argues that a better appreciation of grounds as ‘multivalent’ is important in addressing not only a broad range of disadvantages through affirmative action but also in justifying affirmative action itself as a transformative remedy.